Investigation of under-reporting and the consistency of injury severity classifications in Swedish police crash data compared to hospital injury data based on the Swedish Traffic Accident Data Acquisition (STRADA) - Held, Felix (My University, 2016)
Police reported road crash data is used for Sweden’s official road traffic statistics and is collected by the Swedish TRaffic Accident Data Acquisition (STRADA), which in turn provides a road crash database combining police and emergency hospital reported information. The general goal of this thesis was the investigation of police road crash data from STRADA for the purpose of gaining a deeper understanding of how certain parts of the police data might need to be weighted and how consistent police and hospital injury severity classifications are. Specifically it was investigated how different sub-populations of road crashes are represented in police data and to which extent they were under-reported. Furthermore, the consistency of police and hospital injury severity classifications was investigated. This was achieved by taking advantage of the availability of pre-linked hospital data in STRADA. Data from non-fatal crashes that occurred during the years 2003-2013 were used for the examination of under-reporting of road crashes while those that occurred during the years 2007-2013 were used for the investigation of consistency of injury severity classifications. A direct comparison of the available police and hospital data was used to establish a lower bound for the under-reporting. Capture-recapture methods were used to estimate the actual prevalent amount of under-reporting. Additionally, the longitudinal behaviour of under-reporting was investigated. The influence of different factors on the consistency of injury severity classifications was tested for statistical significance by chi-squared tests and the calculation of odds ratios. In total, under-reporting was found to be at least 48%. This lower bound decreased to 35% when single bicycle crashes were excluded. Two groups of months that consistently exhibited distinct rates of under-reporting were identified and crash severity was identified as a large influence on the amount of under-reporting. A dependence of under-reporting on the involved vehicles was found as well. For the investigation of the consistency of police and hospital reported classifications of injury severity it was found that male gender, age above 60, ambulance or helicopter transport and a rural traffic environment lead to higher odds for different classifications by the police and hospitals compared to their alternatives.
Keywords: Transport; Medicinteknik; Transport; Medical Engineering